NUA 45, a dry bean cultivar, builds a subtle brand in Zimbabwe against all odds - Maereka, Enock; Mutari, Bruce; Kunaka, Fungai; Nchanji, Eileen; Tsekenedza, Shylet; Muthoni-Andriatsitohaina, Rachel; Chimboza, Denford (Frontiers Media, 2024)
Global business today is driven by brands, each with a unique story, but rarely of a product that is a public good. Building a brand requires careful planning, creativity, and an understanding of the target market. Borrowing from various brand concepts and frameworks, this paper explores how a government-bred common bean cultivar., NUA 45, defied the odds to create a new identity and association in Zimbabwe. Firstly, the cultivar overcame the general lack of promotion investment in government-bred (public) common bean cultivars. Secondly, being a red mottle-colored cultivar in a red-speckled (sugar type) bean-predominated country, NUA 45 had to break the preference typecasts. Thirdly, NUA 45 was among the first generation of biofortified bean cultivars enriched with iron (Fe) and zinc (Zn), some of the most sought-after micronutrients in a world ridden with hidden hunger. Overcoming these market barriers required a systematic approach to awareness creation, collaboration, and commercialization, avoiding the tragedy of the commons, and instead, achieving a win-win situation for all stakeholders. This entailed understanding the needs and preferences of different value chain actors, developing messages, and engaging local farmers, retailers, aggregators, and private and public sector partners to promote NUA 45. Lastly, developing compelling stories and leveraging digital channels to reach new customers that sought personal experiences, moved the cultivar name from a mere label to a spontaneously endorsed lifestyle and a brand that ‘spread like wildfire’ across the country and the Southern Africa Development Community (SADC) region. The NUA 45 brand broke new ground for other biofortified bean cultivars and non-sugar bean cultivars. Following its release in seven other countries, NUA 45 pioneered listing on the SADC regional variety catalog.